2022
DOI: 10.4168/aair.2022.14.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Biomarkers Beyond Leukotrienes for the Management of Nonsteroidal Anti-inflammatory Drug (NSAID)-Exacerbated Respiratory Disease

Abstract: Nonsteroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (NERD) is a unique condition characterized by aspirin/NSAID hypersensitivity, adult-onset asthma, and/or chronic rhinosinusitis with nasal polyps. Arachidonic acid metabolism dysregulation and intense eosinophilic/type 2 inflammation are central mechanisms in NERD. Studies have been conducted on various biomarkers, and urinary leukotriene E4 is considered the most available biomarker of NERD. However, the pathophysiology of NERD is het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…AERD pathogenesis is also complicated by other various inflammatory cells, including ILC2 cells, epithelial cells, plasma cells, and platelets, which have rarely been investigated. 38,39 The novel biomarkers for neutrophilic inflammation and airway remodelling in severe asthma should be investigated in AERD as a distinct phenotype of severe asthma. 40,41 In our study, the AERD group had significantly lower serum SPD/MPO levels and higher serum with severe asthma.…”
Section: Discussionmentioning
confidence: 99%
“…AERD pathogenesis is also complicated by other various inflammatory cells, including ILC2 cells, epithelial cells, plasma cells, and platelets, which have rarely been investigated. 38,39 The novel biomarkers for neutrophilic inflammation and airway remodelling in severe asthma should be investigated in AERD as a distinct phenotype of severe asthma. 40,41 In our study, the AERD group had significantly lower serum SPD/MPO levels and higher serum with severe asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, an increased level of urinary leukotriene E4 (which is a stable and final product of CysLTs) is considered a useful biomarker for the diagnosis of AERD ( 44 ). In addition, this mediator could induce mast cell and ILC2 activation as well as eosinophils recruitment into the upper and lower airway mucosa, enhancing persistent type2/eosinophilic inflammation in the upper and lower airways of patients with AERD and resulting in poor clinical outcomes of AERD ( 45 46 ).…”
Section: Asthma and Immune Cellsmentioning
confidence: 99%
“…AERD represents a distinct endotype with dysregulation of arachidonic acid metabolism and upregulated T H 2 inflammation. 14 Overproduction of cysteinyl leukotrienes which potentially induce eosinophilic inflammation is the hallmark of AERD in pathogenic mechanism. It has been reported that asthmatics with AERD are most likely to have severe disease, which has a higher risk of UA, SA, and AE.…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin‐exacerbated respiratory disease (AERD) is characterized by asthma, chronic rhinosinusitis with nasal polyp, and hypersensitivity to nonsteroidal anti‐inflammatory drugs (NSAIDs)/aspirin. AERD represents a distinct endotype with dysregulation of arachidonic acid metabolism and upregulated T H 2 inflammation 14 . Overproduction of cysteinyl leukotrienes which potentially induce eosinophilic inflammation is the hallmark of AERD in pathogenic mechanism.…”
Section: Introductionmentioning
confidence: 99%